Design of improved controller for thermoelectric generator used in distributed generation - Molina, Marcelo Gustavo (2010)
This paper investigates the application of thermal generation based on solid-state devices such as thermoelectric generators (TEGs) as a novel technological alternative of distributed generation (DG). The full detailed modeling and the dynamic simulation of a three-phase grid-connected TEG used as a dispersed generator is studied. Moreover, a new control scheme of the TEG is proposed, which consists of a multi-level hierarchical structure and incorporates a maximum power point tracker (MPPT) for better use of the thermal resource. In addition, reactive power compensation of the electric grid is included, operating simultaneously and independently of the active power generation. Validation of models and control schemes is performed by using the MATLAB/Simulink environment. Moreover, a small-scale TEG experimental set-up was employed to demonstrate the accuracy of proposed models.